Direct broadcast on TV (Eurasian Journal of Philology Science and Education, 2016)
The research paper deals with the skills in the management of direct transmission of television, culture journalist speech, as well as drawbacks existing in the industry, specific ways to strengthen ties with the viewers. Currently in the country as compared to the previous period significantly increased the number of TV channels. Employees of public and commercial television sitematicheskuyu carry out work on the mass propaganda of the main directions of development of an independent, sovereign country, its diverse politics, culture and way of life, social status in market conditions. The most important and joyful that currently there is a sufficient number of highly qualified journalists, as well as modern technical equipment. In this regard, it is time to pay attention not only the quantity but also on the quality of programs. It is essential that television editor carefully and meticulously prepared for each transmission. He must contact the transfer of participants to conduct training in their introduction to the topic of the forthcoming program.
Keywords: television; professional skills; viewership; commercial TV channels; TV editor; presenter